2021
DOI: 10.3390/molecules26216379
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Lycopodiaceae Alkaloids and Evaluation of Their Anticholinesterase and Cytotoxic Activities

Abstract: In view of the abundant evidence that Lycopodiaceae alkaloids, including the well-known huperzine A (HupA), are among the potent acetylcholinesterase (AChE) inhibitors, an attempt was made to search for new compounds responsible for this property. For this purpose, three plant species belonging to the Lycopodiaceae family, commonly found in the Euro-Asia region, were subjected to the isolation of bioactive compounds, their identification and subsequent evaluation of their anticholinesterase and cytotoxic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Many of the studies on the Lycopodiaceae alkaloids were carried out in the second half of the 20th century. They led to the isolation of more than 200 alkaloids, which were then divided by Canadian scientists in the 1990s into four major classes based on similarities in structure and pharmacological activity, including lycopodine, lycodine, fawcettimine and miscellaneous [ 34 ]. Alkaloids belonging to the lycopodine type with a single nitrogen atom in their structure constitute the largest group with more than 100 compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the studies on the Lycopodiaceae alkaloids were carried out in the second half of the 20th century. They led to the isolation of more than 200 alkaloids, which were then divided by Canadian scientists in the 1990s into four major classes based on similarities in structure and pharmacological activity, including lycopodine, lycodine, fawcettimine and miscellaneous [ 34 ]. Alkaloids belonging to the lycopodine type with a single nitrogen atom in their structure constitute the largest group with more than 100 compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, researchers have proven that the alkaloid huperzine A (HupA), isolated from the Huperzia species (the Lycopodiaceae family), penetrates better the blood–brain barrier, has higher bioavailability and is less toxic compared to known AChE inhibitors (e.g., galantamine). Furthermore, recent studies in Huperzia , as well as Lycopodium species , confirmed the presence of novel potent AChE inhibitors in vitro assays [ 34 ]. Angelica dahurica (Hoffm.)…”
Section: Introductionmentioning
confidence: 94%
“…Pure compounds were obtained from active fractions by high-performance liquid chromatography (HPLC, L-2130, Hitachi, Tokyo, Japan) with a preparative 9.4 × 250 mm Zorbax Sil column (5 μm). The isocratic mobile phase consisted of n -hexane (90%) and ethyl acetate (10%), at a flow rate of 2 mL/min; elution peaks were detected by the refractive index (RI) detector [ 34 , 35 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…L. clavatum is a rich source of alkaloids and triterpenoids. Recently, Dymek et al (2021) developed a technique to extract L. clavatum, L. annotinum, and H. selago active ingredients by using the pressurized liquid extraction method. These methanolic extracts showed bioactivity as anti-AChE (Dymek et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dymek et al (2021) developed a technique to extract L. clavatum, L. annotinum, and H. selago active ingredients by using the pressurized liquid extraction method. These methanolic extracts showed bioactivity as anti-AChE (Dymek et al 2021). Three new triterpenoids of L. clavatum were isolated from the methanol extract via combined chromatographic separation techniques.…”
Section: Introductionmentioning
confidence: 99%